Analysis of The Effect of Liquidity, Leverage, and Size on Roa (Case Study of Telecommunication Companies Listed on The IDX for The 2017-2021 Period) - Nur Kamilah; Ratih Kusumawardhani; Alfiatul Maulida (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
Analysis of the influence of liquidity, leverage, and size on return on assets (case study of Tbk Telecommunication Company 2017-2021) listed on the Indonesia Stock Exchange. Aims to answer the problem regarding the influence of liquidity, leverage and size on return on assets (case study of a telecommunications company). In this research the method used is a quantitative approach. The results of the research show that the variable current ratio (X1) has a significant influence on return on assets (Y). Then the cash ratio (X1) variable does not have a significant effect on return on assets (Y). Variable debt to equity ratio (X2) has a significant influence on return on assets (Y). And the size variable (X3) does not have a significant effect on return on assets (Y). And from the results of the f test it is proven that the current ratio, cash ratio, debt to equity, size have a simultaneous effect on return on assets (Y).